Text-fading based training leads to transfer effects on children's sentence reading fluency - Nagler, Telse; Korinth, Sebastian P.; Linkersdörfer, Janosch; Lonnemann, Jan; Rump, Björn; Hasselhorn, Marcus; Lindberg, Sven (Frontiers in Psychology, 2015)
Previous studies used a text-fading procedure as a training tool with the goal to increase silent reading fluency (i.e., proficient reading rate and comprehension). In recently published studies, this procedure resulted in lasting reading enhancements for adult and adolescent research samples. However, studies working with children reported mixed results. While reading rate improvements were observable for Dutch reading children in a text-fading training study, reading fluency improvements in standardized reading tests post-training attributable to the fading manipulation were not detectable. These results raise the question of whether text-fading training is not effective for children or whether research design issues have concealed possible transfer effects. Hence, the present study sought to investigate possible transfer effects resulting from a text-fading based reading training program, using a modified research design. Over a period of three weeks, two groups of German third-graders read sentences either with an adaptive text-fading procedure or at their self-paced reading rate. A standardized test measuring reading fluency at the word, sentence, and text level was conducted pre- and post-training. Text level reading fluency improved for both groups equally. Post-training gains at the word level were found for the text-fading group, however, no significant interaction between groups was revealed for word reading fluency. Sentence level reading fluency gains were found for the text-fading group, which significantly differed from the group of children reading at their self-paced reading routine. These findings provide evidence for the efficacy of text-fading as a training method for sentence reading fluency improvement also for children.